KARAKTERISTIK PAPAN PARTIKEL DARI CAMPURAN LIMBAH AKASIA (Acacia mangium Willd.) DAN KULIT KELAPA MUDA (Cocos nucifera L.): Characteristics of Particle Board from Mixed Waste of Acacia (Acacia mangium Willd.) and Coconut Shell (Cocos nucifera L. - Anggraini, Riana; Khabibi, Jauhar; Adelka, Yunia Frida (Fakultas Kehutanan Universitas Jambi, 2021)
The aim of this research is to make an effort to utilize forestry waste, in the form of harvesting waste of acacia (Acacia mangiumWilld.) and coconut shells (Cocos nucifera L.) into particle boards by considering the evaluation of the value of particle board characteristics, both physical and mechanical characteristics in accordance with standards JIS A 5908-2003.This study used a factorial analysis where the first factor was the composition of the raw material for acacia: coconut (100: 0, 60:40, 50:50, 40:60 and 0:100). While the second factor is the provision of pretreatment on particles (cold soak, hot soak and without immersion).This analysis was carried out in a completely randomized design (CRD) with three repetitions.The results showed that the composition of the raw materials had a significant effect on the value of water content, water absorption, modulus of rupture and modulus of elasticity.The pretreatment had a significant effect on the thickness swelling, water absorption, modulus of rupture and modulus of elasticity. Meanwhile, the interaction of these two factors has a significant effect on the internal bond value, modulus of rupture and modulus of elasticity.Based on the results, it is known that only the density parameters that meet the JIS A 5908-2003 standard, the moisture content and thickness development parameters have not met the standards, while the mechanical characteristics of the particle board have not met the standards.Overall particle board with the composition of acacia raw material: young coconut 60:40 and heat soaking pre-treatment can produce good quality particle board.